Regular Education Initiative The General Educator's Responsibility - Kolliopoulos, Theofani ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This report discusses the Regular Education Initiative (REI) and how it is currently being implemented in a middle school in Illinois, how it potentially benefits students, and how to promote use of accommodations by all teachers. Accommodations and modification appropriate to the Individualized Education Programs (IEPs) of nine students with learning disabilities, as well as compensatory strategies to promote independent learning, were integrated into the regular education content matter of the teacher-researcher's classroom. While the accommodations and modifications had to be tailored to each targeted student, compensatory strategies could be taught to the entire class. Appropriate accommodations and modifications were started as early as the first day of school in order to make them a regular part of the class routine. Examples of accommodations included extended time, shortened writing assignments, study guides or sheets, pre-copied notes, modified tests and quizzes, tests and quizzes read aloud, rephrasing of questions and/or directions, books on tape, and technology such as word processing and spell checkers. Over the 10 weeks in which the intervention was implemented, 5 out of the 9 students demonstrated positive academic performance. The other four students exhibited fluctuating periods of positive and negative academic performance. (CR)
ERIC Note: Master of Arts Action Research Project, Saint Xavier University and IRI/Skylight Professional Development Field-Based Master's Program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Accommodations (Disabilities); Academic Achievement; Classroom Techniques; Inclusive Schools; Instructional Effectiveness; Learning Disabilities; Middle School Students; Middle Schools; Testing Accommodations (Disabilities); Dissertations/Theses.